Prevalência de recessão gengival e fatores associados em uma população rural do sul do Brasil - Casarin, Maísa (2018)
Gingival recessions (GR) have not been considered a major concern in periodontal epidemiology, despite numerous intervention studies evaluating aesthetic approaches. In addition, studies evaluating this outcome in a population are scarce and have methodological limitations, such as a convenience sample and the use of partial periodontal examination protocols. Epidemiological research in dentistry allows the investigation of the oral health status of populations and is considered fundamental for oral health goals are reached and for the formulation of effective health policies. Thus, the present thesis is composed of two scientific articles, whose main theme is gingival recession (GR) in a representative sample of the rural area. The first article aims to analyze the prevalence and associated factors of 617 detate individuals ≥15 years. Six sites per tooth were clinically evaluated and three cut-off points were used to perform multilevel analysis, GR ≥1mm, ≥3mm and ≥5mm. The prevalence and extent of GR ≥ 1 mm was 99.7%, and 14.17, respectively. Periodontitis and age were associated with GR at all cut-off points, while low schooling was associated with RG ≥1mm and ≥3mm, and low income and smokers or former smokers were associated with RG ≥3mm and ≥5mm. In addition, brushing frequency <2x/day was associated as a protective factor for RG ≥1mm. In article 2, the objective was to evaluate the estimates and a multilevel analysis of the associated factors with GR in patients without severe periodontitis living in the rural area. Two hundred and eighty-two individuals without severe periodontitis with ≥20 teeth were analyzed. Two cut-off points for RG were used, ≥1mm and ≥3mm. In addition, in the multilevel analysis, older age, low schooling, and molar and pre molar teeth were associated with RG ≥1mm and ≥3mm, and supragingival calculus and individuals smokers and/or former smokers were associated with RG ≥1mm and ≥3mm, respectively. Frequency of brushing <2x/day was a protective factor for RG ≥1mm and ≥3mm. The results found in this study serve as a basis for providing information to generate health strategies to reduce the prevalence and consequences of GR in individuals living in rural areas.